Metformin versus Insulin for Gestational Diabetes: A Randomized Clinical Trial - Agrawal, Ajay; Chhetri, Shailaja; Agrawal, Jyoti; Maskey, Robin (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Background: Insulin therapy is often started if medical nutritional therapy (MNT) fails to manage Gestational diabetes mellitus (GDM) which is associated with multiple injections and demands more patient compliance. So use of safe and effective oral agents may offer advantages over insulin. Objectives: To evaluate glycaemic control in women receiving metformin versus insulin for GDM, and to identify factors predicting the need for supplemental insulin in women initially treated with metformin. Methods: Women, 18 – 45 years at 20 –33 weeks of gestation with singleton pregnancy with GDM without satisfactory glycemic control on MNT for a minimum period of 1 week were randomised to receive either insulin or metformin. Results: There was no significant difference in mean pre-treatment glucose levels between two groups (P = 0.890). After randomizing, women received their respective intervention. Mean glucose level measured after glycaemic control showed, lower levels in the metformin group (P= .034). Also women under metformin presented less weight gain (P=.02) and a lower frequency of neonatal hypoglycaemia (P= .032). Thirteen women in the metformin group (31.7%) required supplemental insulin. Early gestational age at diagnosis and high BMI were identified as predictors of the need for supplemental insulin. Conclusions: Metformin appears to constitute safe and effective treatment option for GDM who do not have satisfactory glycemic control. It was found to provide adequate glycemic control with lower mean glucose level, less weight gain and a lower frequency of neonatal hypoglycaemia. Early gestational age at diagnosis and high BMI were predictors of the need for supplemental insulin therapy in women initially treated with metformin.